Hypoxia Affects the Antioxidant Activity of Glutaredoxin 3 in Scylla paramamosain through Hypoxia Response Elements - Yu-Kun Jie; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Jian-Jun Jiang; Zhi-Xun Guo (MDPI AG, 2022)
Hypoxia is a major environmental stressor that can damage the oxidation metabolism of crustaceans. Glutaredoxin (Grx) is a key member of the thioredoxin superfamily and plays an important role in the host's defense against oxidative stress. At present, the role of Grx in response to hypoxia in crustaceans remains unclear. In this study, the full-length cDNA of Grx3 (SpGrx3) was obtained from the mud crab Scylla paramamosain, which contains a 129-bp 5' untranslated region, a 981-bp open reading frame, and a 1,183-bp 3' untranslated region. The putative SpGrx3 protein contains an N-terminal thioredoxin domain and two C-terminal Grx domains. SpGrx3 was expressed in all tissues examined, with the highest expression in the anterior gills. After hypoxia, SpGrx3 expression was significantly up-regulated in the anterior gills of mud crabs. The expression of Grx2 and glutathione S-transferases was decreased, while the expression of glutathione peroxidases was increased following hypoxia when SpGrx3 was silenced in vivo. In addition, the total antioxidant capacity of SpGrx3-interfered mud crabs was significantly decreased, and the malondialdehyde content was significantly increased during hypoxia. The subcellular localization data indicated that SpGrx3 was predominantly localized in the nucleus when expressed in Drosophila Schneider 2 (S2) cells. Moreover, overexpression of SpGrx3 reduced the content of reactive oxygen species in S2 cells during hypoxia. To further investigate the transactivation mechanism of SpGrx3 during hypoxia, the promoter region of the SpGrx3 was obtained by Genome Walking and three hypoxia response elements (HREs) were predicted. Dual-luciferase reporter assay results demonstrated that SpGrx3 was likely involved in the hypoxia-inducible factor-1 (HIF-1) pathway during hypoxia, which could be mediated through HREs. The results indicated that SpGrx3 is involved in regulating the antioxidant system of mud crabs and plays a critical role in the response to hypoxia.